PLANNING OF SERVICE ROAD THICK PAVEMENT FROM THE NEW TERMINAL TO THE CARGO TERMINAL AT H.HASAN AROEBOSMAN AIRPORT ENDE - Dwi Kardianto, Rachmad; Winiasri, Linda; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
H.Hasan Aroeboesman Ende Airport Class II is managed by the Ministry of Transportation which is located in Ende district, East Nusa Tenggara province. H.Hasan Aroeboesman Ende Airport has a runway dimension of 1650mx30m with the largest operating aircraft, namely ATR 72-600. At this time H.Hasan Aroeboesman Ende Airport does not yet have a Service Road that connects the new terminal with the old terminal which is now being converted into a terminal cargo. additional supporting facilities in the form of a Service Road using flexible pavement which functions as an operational road for the Ground Support Equipment team in order to improve the security and safety aspects of flight operations which are urgently needed at H. Hasan Aroeboesman Ende Airport. This Service Road planning study uses the component analysis method which refers to the calculations of SNI-1731-1989-F. to determine the width of the Service Road according to the needs to be planned. Then determine the thickness of the pavement design and the strength of the pavement required at the time of planning. And determine the budget plan that will be needed in the Service Road planning process at H. Hasan Aroeboesman Ende airport. The unit price of work refers to SNI and PM 78 of 2014. For the results of the analysis and calculations that have been carried out, the length of the inspection road is 150 m with a width of 4 meters, the thickness of the individual inspection road pavement is 45 cm with a surface course layer thickness of 5 cm, a base course of 20 cm, and a subbase course of 20 cm, and the total price for planning the construction of the inspection road is 390,1 million rupiah.